Multivariate analysis of pomological and morphological diversity in Withania coagulans, a neglected medicinal plant - Ali Khadivi; Farhad Mirheidari; Yazgan Tunç; Abdolvahid Saeidifar; Younes Moradi (Scientific Reports)
Abstract Withania coagulans (Stocks) Dunal, a medicinally important species from the Solanaceae family, remains underexplored in terms of its morphological and pomological diversity. Understanding its phenotypic variability is vital for genetic conservation and breeding efforts targeting improved fruit and seed traits. This study evaluated 43 morphological and pomological traits in accessions collected from five regions in Sistan-va-Baluchestan, Iran. Substantial phenotypic variation was observed, with plant height ranging from 60 cm (‘Rachedr-10’) to 200 cm (‘Kahiri-11’). Fruit weight was strongly correlated with seed weight (r = 0.83, p < 0.01), and multiple regression analysis identified fruit weight (β = 0.79, p < 0.00) as the most significant predictor of seed output. Principal component analysis (PCA) showed that the first three components explained 31.63% of the total variation, mainly influenced by fruit weight, seed weight, and leaf dimensions. Heat map analysis grouped accessions into distinct clusters, with ‘Kahiri-8’, ‘Malekabad-15’, and ‘Rachedr-6’ exhibiting superior fruit traits, while ‘Hit-8’, ‘Veshder-8’, and ‘Malekabad-11’ were prominent in vegetative features. The identified phenotypic diversity and clustering patterns reflect potential genetic differentiation and local adaptation. Accessions with desirable fruit traits represent promising candidates for future breeding programs. The findings demonstrate the effectiveness of multivariate analysis in germplasm characterization of W. coagulans.